The VESPA Project: Virtual Reality Interventions for Neurocognitive and Developmental Disorders - Emanuele Maria Merlo; Liam Alexander MacKenzie Myles; Salvatore Marco Pappalardo (Journal of Mind and Medical Sciences)
VESPA is a financed project supported by the Sicilian Regional Research and Development funds, and it is structured by the development, research and validation of Virtual Reality (VR) based application for the diagnosis and treatment of neurocognitive conditions. In particular, this article presents its characteristics, referred to as the first (2013-2015) and second (2021-ongoing) generations of VESPA, with particular reference to literature regarding the VR technology application and development, the VR treatment of neurocognitive conditions and prior versions of this intervention. Through a comprehensive review of the research conducted over the last 5 years, evidence has emerged supporting VESPA’s aim and scopes, highlighting how the application of VR can be considered to add value to typical rehabilitation/therapeutic paths. VESPA project generations are then presented in detail, including specific session/task battery characteristics, 2.5D, 3D and 5D typologies, system usability and architecture and pathological domain-based dynamics and features. The discussion about VESPA will highlight the current advantages along with limitations and future directions.